The Primary Sources of Interruptions Experienced by Physicians and Nurses in Emergency Departments: A Scoping Review - Emadi, Navaz; Mojtahedzadeh, Rita; Allameh, Seyyed Farshad; Basiri, Kamal; Mohammadi, Aeen (Archives of Academic Emergency Medicine, 2026)
Introduction: Interruptions are common in emergency departments (ED) and frequently occur during critical clinical tasks. These interruptions disrupt workflow, reduce situational awareness, increase the risk of errors, and may compromise patient safety. Identifying and mapping their sources is therefore essential to guide targeted strategies and improve the quality of care. This scoping review aimed to identify and categorize the primary sources of work-related interruptions among physicians and nurses in the ED. Methods: The review question, developed using the PCC framework (physicians and nurses; work-related interruptions; EDs), sought to identify the primary sources of interruptions in ED settings. A comprehensive search was performed in PubMed, Scopus, Embase, Web of Science, and Google Scholar to locate peer-reviewed studies published up to September 2025. Two reviewers independently screened the studies and extracted the data. Results: A total of 12 studies met the inclusion criteria. Reported interruption rates varied across settings and professional roles. The primary sources of interruptions were grouped into six major categories: colleague interference, phone and pager alerts, patient-initiated interruptions, family or companion interference, technical failures and lack of resources, and environmental noise. Most interruptions occurred at nursing or physician workstations and during medication preparation, documentation, or direct patient care. Conclusion: This scoping review provides a comprehensive overview of the main sources of interruptions in ED. Understanding where and why these interruptions occur can guide the development of targeted educational, organizational, and environmental interventions. Reducing avoidable interruptions may enhance staff performance, improve patient safety, and optimize the quality of emergency care.